Towards developing a marketing model for strategic positioning of stingless bee honey farming as a sustainable income for the rural community - Kassim, Salina; Hussin, Siti Rahayu (Federal Agricultural Marketing Authority, 2022)
Due to its wide economic applications and low initial costs, stingless bee farming has a high potential to be developed as an economic empowerment program for the low income community in the rural area. Despite this, in-depth research focusing on the marketing aspects of stingless bee farming is still lacking resulting in a sub-optimal production level as well as low profitability of the stingless bee farms generally. This study aims to focus on the issues pertaining to marketing aspects of the stingless honey bee farming in order to develop a marketing model to position it as a sustainable economic empowerment program for the low income community in the rural areas.